Bioactive components of endophytic fungi from two Hainan mangrove plants - CHEN Biting; WU Weicheng; ZHOU Dongdong; DENG Xiaolin; ZHANG Shiqing; YUAN Jingzhe; XU Jing; GUO Zhikai (Shenzhen Daxue xuebao. Ligong ban)
Mangrove endophytic fungi are one of the important sources for discovering natural drug leads. In order to obtain natural compounds with novel structures, the metabolites of two mangrove endophytic fungi Phomopsis sp. DHS11 and Aspergillus fumigatus JRJ111048 were studied. As a result, nine compounds (1-9) were isolated from their fermentation extract by comprehensive silica gel, reverse phase silica gel, Sephadex LH20 column chromatography and high performance liquid chromatography (HPLC). The structures of these compounds were identified as norpestaphthalide C (1), norpestaphthalide A (2-a), norpestaphthalide B (2-b), 7-hydroxy-3-(2-hydroxy-propyl)-5-methyl-isochromen-1-one (3), alternaroside B (4), cytochalasin B (5), cerevisterol (6), 5-hydroxymethyl-furaldehyde (7), N-(4-hydroxyphenethyl) acetamide (8), 3,5-dihydroxybenzoic acid (9) by using high resolution electrospray mass spectrometry (HRESIMS), nuclear magnetic resonance spectroscopy (NMR), optical rotation, ultraviolet, infrared spectroscopy techniques and comparing with reported data. Among them, compound 1 was a new benzofuranone-type natural compound discovered for the first time, and the compound 4 was a cerebroside-type natural product reported for the first time from Phomopsis sp. The immunosuppressive activity, antitumor activity and anti-Alzheimer's activity of compounds 1-9 were evaluated. The result showed that compound 5 displayed good immunosuppressive activity. The research results provide new clues for the in-depth exploration of new bioactive substances in mangrove endophytes.